Viral hepatitis: Guidelines by the American Society of Transplantation Infectious Disease Community of Practice. Issue 9 (14th April 2019) - Te, Helen; Doucette, Karen
Abstract: These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention, and management of viral hepatitis in the pre‐ and post‐transplant period. The current guidelines reflect the declining need for hepatitis B immunoglobulin following liver transplant, now replaced with nucleos(t)ide analogues that effectively suppress viral replication for the long term with minimal risk for drug resistance. It describes the limitations of pegylated interferon alpha in the treatment for chronic hepatitis D. The guidelines feature the paradigm shift in the treatment arena of chronic hepatitis C, now consisting of highly effective direct‐acting antiviral (DAA) medications that effect a cure almost universally. Its safety profile and easy tolerance have permitted its use in patients with decompensated cirrhosis and/or end‐stage renal disease. The high potency of the DAA's has fueled the rapidly expanding utilization of hepatitis C‐exposed grafts in non‐hepatitis C‐infected liver, heart, or kidney recipients within structured protocols, followed by viral eradication with DAA therapy in the peri‐ or post‐transplant period. Chronic hepatitis E has become more recognized in the solid‐organ transplant recipients, and the therapeutic approach has been streamlined to start with reduction of immunosuppression, and if indicated afterward, ribavirin monotherapy.